(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Cysts of the paranasal sinuses are benign, often asymptomatic formations. Most often, cysts are found in the maxillary sinuses (MSS). The purpose of the study is to summarize modern publications on diagnostics and treatment tactics for intracranial cysts. Material and methods. The review used publications presented in the information databases eLIBRARY, PubMed/MEDLINE, ScienceDirect, EBSCO, for the period from 2010 to 2024, which were found using the keywords: maxillary sinus cyst, clinical course, treatment. The analysis includes original studies on the problem of diagnosis and treatment of maxillary sinus cysts, as well as analytical reviews.